Synthesis of hydrocortisone esters targeting androgen and glucocorticoid receptors in prostate cancer in vitro - Peřina, Miroslav; Kiss, Anita; Mernyák, Erzsébet; Mada, Lukáš; Schneider, Gyula; Jorda, Radek (The Journal of steroid biochemistry and molecular biology, 2023)
Androgen and glucocorticoid receptors have been recently described as key players in processes related to prostate cancer and mainly androgen receptor's inactivation was shown as an effective way for the prostate cancer treatment. Unfortunately, androgen deprivation therapy usually loses its effectivity and the disease frequently progresses into castration-resistant prostate cancer with poor prognosis. The role of the glucocorticoid receptor is associated with the mechanism of resistance; therefore, pharmacological targeting of glucocorticoid receptor in combination with antiandrogen treatment was shown as an alternative approach in the prostate cancer treatment. We introduce here the synthesis of novel 17α- and/or 21-ester or carbamate derivatives of hydrocortisone and evaluation of their biological activity towards androgen and glucocorticoid receptors in different prostate cancer cell lines. A 17α-butyryloxy-21-(alkyl)carbamoyloxy derivative 14 was found to diminish the transcriptional activity of both receptors (in single-digit micromolar range), with comparable potency to enzalutamide towards the androgen receptor, but weaker potency compared to mifepristone towards the glucocorticoid receptor. Lead compound inhibited proliferation and the formation of cell colonies in both androgen and glucocortiocid receptors-positive prostate cancer cell lines in low micromolar concentrations. Candidate compound 14 showed to interact with both receptors in cells and inhibited the translocation of receptors to nucleus and their activation phoshorylation. Moreover, binding to receptor's ligand binding domains was assessed by molecular modelling. Lead compound also induced the accumulation of cells in G1 phase and its combination with enzalutamide was shown to be more effective than enzalutamide alone.
Keywords: signální transdukce; Nitriles; Transcriptional activity; Prostatic Neoplasms, Castration-Resistant; Androgen Antagonists; Receptors, Androgen; Receptors, Glucocorticoid; Humans; lidé; Hydrocortisone; Glucocorticoid receptor; antagonisté androgenů; hydrokortison; Drug Resistance, Neoplasm; androgeny; receptory glukokortikoidů; chemorezistence; nádory prostaty rezistentní na kastraci; Hydrocortisone derivatives; Male; Androgen receptor; nitrily; Castration resistant prostate cancer; Androgens; mužské pohlaví; Prostate cancer; nádorové buněčné linie; Cell Line, Tumor; Signal Transduction; androgenní receptory